Managerial Social Capital and Financial Development: A Cross‐Country Analysis. Issue 1 (February 2016) - Javakhadze, David; Ferris, Stephen P.; French, Dan W.
Abstract: This study examines the issue of whether managerial social capital, defined as aggregate benefits of social obligations and informal contacts formed through social networks, has an impact on financial development. Utilizing a large cross‐country sample for the period 1999–2012, we provide evidence that higher levels of social capital have a positive effect on financial development. We are able to examine different types of social connections for our sample firms and find that informal and nonprofessional relationships matter the most for financial market development. These findings are robust to alternative model specifications, variable measurement, and estimation techniques.